2013
DOI: 10.15446/ing.investig.v33n2.39517
|View full text |Cite
|
Sign up to set email alerts
|

Developing high-performance concrete incorporating highly-reactive rice husk ash

Abstract: The aim of this study is to present results of an investigation about the developing of a high-performance concrete (HPC) using a highly reactive pozzolan made from chemically treated rice husk ash (ChRHA) prepared by a chemical-thermal attack to the rice husk. This particular rice husk ash (RHA) consists of 99% of silica, highly amorphous, white in color and of greater pozzolanic activity than the silica fume and another rice husk ash prepared with only by a thermal treatment. The results of the physical, che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The percentage of crystalline phases in the GGBFS and FA were analyzed using Rietveld, and the percentage of amorphous fraction was calculated by difference (see Tables 4 and 5). The amorphous properties of the materials used were within acceptable limits and that adequate cementitious properties can be expected [50]. The experimental program consisted of two stages (a) alkali-activated prepared in the first stage, based on a 50% replacement of OPC with GGBFS, FA, and (b) 30% replacement without activation (see Table 6).…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of crystalline phases in the GGBFS and FA were analyzed using Rietveld, and the percentage of amorphous fraction was calculated by difference (see Tables 4 and 5). The amorphous properties of the materials used were within acceptable limits and that adequate cementitious properties can be expected [50]. The experimental program consisted of two stages (a) alkali-activated prepared in the first stage, based on a 50% replacement of OPC with GGBFS, FA, and (b) 30% replacement without activation (see Table 6).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies used RHA as partial and full replacements to cement to produce a high-performance concrete. Salas et al [14] used the highly reactive RHA and observed that 10% of a high reactive RHA is the optimum replacement level to ordinary cement which enhanced the compressive strength, flexural strength, and elastic modulus of concrete. However, using the RHA requires high water requirement.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of this type of ash on the properties of high-performance concrete has not been studied in detail. There are only a few studies on RHA with acid washing [38,42,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%